Phase transformation of strontium hexagonal ferrite - Bilovol, Vitaliy (2015)
The phase transformation of strontium hexagonal ferrite (SrFe12O19) to magnetite (Fe3O4) as main phase and strontium carbonate (SrCO3) as secondary phase is reported here. SrFe12O19 powder was obtained by a heat treatment at 250 °C under controlled oxygen flow. It was observed that the phase transformation occurred when the SrFe12O19 ferrite was heated up to 625 °C in confinement conditions. This transformation took place by a combination of three factors: the presence of stresses in the crystal lattice of SrFe12O19 due to a low synthesis temperature, the reduction of Fe3þ to Fe2þ during the heating up to 625 °C, and the similarity of the coordination spheres of the iron atoms present in the S-block of SrFe12O19 and Fe3O4. X-ray diffraction analysis confirmed the existence of strain and crystal deformation in SrFe12O19 and the absence of them in the material after the phase transformation. Dispersive X-ray absorption spectroscopy and Fe57 Mössbauer spectroscopy provided evidences of the reduction of Fe3þ to Fe2þ in the SrFe12O19 crystal.